2006
DOI: 10.1161/circulationaha.106.624320
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone Prevents the Development of a Vulnerable Substrate for Atrial Fibrillation in a Canine Model of Heart Failure

Abstract: Background-Atrial fibrosis is an important substrate in atrial fibrillation (AF), particularly in the setting of structural heart disease. In a canine model, congestive heart failure (CHF) produces significant atrial fibrosis and the substrate for sustained AF. This atrial remodeling is a potential therapeutic target. The objective of the present study is to evaluate the effects of the antifibrotic drug pirfenidone (PFD) on arrhythmogenic atrial remodeling in a canine CHF model. Methods and Results-We studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
169
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(177 citation statements)
references
References 48 publications
6
169
0
2
Order By: Relevance
“…14 There are a few reports concerning the effect of pirfenidone on heart diseases. Lee et al 30 investigated the effects of pirfenidone on arrhythmogenic atrial remodeling with ventricular tachypacinginduced chronic heart failure in canines. In their study, pirfenidone treatment resulted in a significant reduction of atrial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…14 There are a few reports concerning the effect of pirfenidone on heart diseases. Lee et al 30 investigated the effects of pirfenidone on arrhythmogenic atrial remodeling with ventricular tachypacinginduced chronic heart failure in canines. In their study, pirfenidone treatment resulted in a significant reduction of atrial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…17 Atrial interstitial fibrosis has been shown to increase with age in humans and has been observed in patients with AF, 18 in animal models of aging, 19 and in chronic heart failure (CHF). This atrial interstitial fibrosis has been shown to increase AF vulnerability in animal models of CHF 20 and in a transgenic mouse model for selective atrial fibrosis. 2 In our study, we directly found that the value of CVF of LAA in patients with pre-AF were higher than in patients with pre-SR.…”
Section: Ibs and Atrial Fibrosis In Patients With Preoperative Af And Srmentioning
confidence: 96%
“…Atrial fibrosis has been shown to increase AF vulnerability in animal models of heart failure and selective atrial fibrosis. 1,2 Correlative data in biopsy and autopsy specimens from patients with AF have uncovered the presence of atrial fibrosis. 3,4 Postoperative AF (post-AF) is a common problem after coronary bypass grafting (CABG).…”
Section: Introductionmentioning
confidence: 99%
“…This increases heart excitability and should be considered for electrophysiological studies and evaluation of defibrillation strategies. On the contrary, dogs have very close cardiac electrophysiological properties as compared to humans [24]. Therefore, they might be an "ideal" model for arrhythmia studies but their wide use raises ethical and economical issues [25].…”
Section: Large Animal Models Of Cardiac Arrestmentioning
confidence: 99%